Penanaman Nilai Religius Berbasis Pembiasaan dan Keteladanan untuk Penguatan Pendidikan Karakter di Pesantren - ruswinarsih, sigit; Syihabuddin, Syihabuddin; Kosasih, Aceng (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study aims to explore religious values and the process of refraction and exemplary in strengthening the character education of female students at the Darussalim Putri Bati-Bati Islamic Boarding School. Qualitative research is used with a case study approach, and data is collected by means of observation, interviews and documentation, then analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that the religious values that were instilled through the socialization process were the values of aqidah, worship values and moral values. The process of learning and familiarizing religious values occurs every day in order to form a religious moral personality. Based on the learning process, characters with religious values are instilled through habituation in the rules and activities of Islamic boarding schools and exemplary to caregivers, teachers and coaches.